2012
DOI: 10.1111/j.1440-1584.2012.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical appointment no‐shows associated with poor glycaemic control among Taiwanese aborigines

Abstract: Taiwanese aboriginal diabetes patients as a group have poorer glycaemic control than the non-aboriginal group. Medical appointment no-shows may significantly contribute to the development of hyperglycaemia among Taiwanese aborigines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…The results of this study showed a mean HbA1c of 8.6% (SD = + 2.04) which was higher compared to the result of the study conducted by Brian et al among 1,131 T2DM patients in Fiji as part of the HbA1c data collected during the Fiji Eye Health Survey 2009 (mean HbA1c = 6.5%, SD = + 1.3) [28]. The proportion of poor glycaemic control (HbA1c > 7%) in this study was 77.2% which is similar to the results of the previous studies done in Fiji in 2014 by Kumar et al [29] and those conducted in low and middle income countries [29][30][31][32]. Despite stringent glycemic control to prevent complications, generally over 60% of T2DM patients do not achieve the recommended glycemic targets (HbA1c < 7%) [33].…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study showed a mean HbA1c of 8.6% (SD = + 2.04) which was higher compared to the result of the study conducted by Brian et al among 1,131 T2DM patients in Fiji as part of the HbA1c data collected during the Fiji Eye Health Survey 2009 (mean HbA1c = 6.5%, SD = + 1.3) [28]. The proportion of poor glycaemic control (HbA1c > 7%) in this study was 77.2% which is similar to the results of the previous studies done in Fiji in 2014 by Kumar et al [29] and those conducted in low and middle income countries [29][30][31][32]. Despite stringent glycemic control to prevent complications, generally over 60% of T2DM patients do not achieve the recommended glycemic targets (HbA1c < 7%) [33].…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study showed a mean HbA1c of 8.6% (SD = ± 2.04) which was higher compared to the result of the study conducted by Brian et al among 1,131 T2DM patients in Fiji as part of the HbA1c data collected during the Fiji Eye Health Survey 2009 (mean HbA1c = 6.5%, SD = ± 1.3) [28]. The proportion of poor glycaemic control (HbA1c ≥ 7%) in this study was 77.2% which is similar to the results of the previous studies done in Fiji in 2014 by Kumar et al [29] and those conducted in low and middle income countries [29][30][31][32]. Despite stringent glycaemic control to prevent complications, generally over 60% of T2DM patients do not achieve the recommended glycaemic targets (HbA1c < 7%) [33].…”
Section: Discussionsupporting
confidence: 86%
“…Appointment adherence is a health behavior that remains a challenge for health care systems because of its detrimental effects on patient treatment and outcomes. [3][4][5] However, appointment adherence has received little attention as a behavioral issue, compared with, for example, treatment adherence, or immunization uptake. 42 This study examined whether an intervention implementing fees for unscheduled visits would result in improving appointment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…For patients, missed appointments result in poor treatment adherence, disruption of multidisciplinary health care, and difficulty in patient-provider relationship. 3 They are also associated with increased risk of rehospitalization, 4,5 poor control of chronic conditions, 3,5 and can affect the health of other patients who lose the opportunity to receive timely care. 6 For health care providers, missed appointments reduce the chance of junior physicians to learn from different cases, 7 and could lead to staff underutilization, lower productivity, and increased costs.…”
Section: Introductionmentioning
confidence: 99%